Intrinsic Fluorescence of the Active and the Inactive Functional Forms of Human Thymidylate Synthase. (26th March 2021) - Vitiello, Simone; Caselli, Monica; Pavesi, Giorgia; Santucci, Matteo; Ferrari, Stefania; Paola Costi, Maria; Ponterini, Glauco
Abstract: The observables associated with protein intrinsic fluorescence – spectra, time decays, anisotropies – offer opportunities to monitor in real time and non‐invasively a protein's functional form and its interchange with other forms with different functions. We employed these observables to sketch the fluorometric profiles of two functional forms of human thymidylate synthase (hTS), a homodimeric enzyme crucial for cell proliferation and thus targeted by anticancer drugs. The protein takes an active and an inactive form. Stabilization of the latter by peptides that, unlike classical hTS inhibitors, bind it at the monomer/monomer interface offers an alternative inhibition mechanism that promises to avoid the onset of drug resistance in anticancer therapy. The fluorescence features depicted herein can be used as tools to identify and quantify each of the two protein forms in solution, thus making it possible to investigate the kinetic and thermodynamic aspects of the active/inactive conformational interchange. Two examples of fluorometrically monitored interconversion kinetics are provided. Abstract : A matter of form : The active and the inactive functional forms of human thymidylate synthase, a long‐known anticancer target, exhibit different intrinsic fluorescence spectra, quantum yields, lifetime profiles and anisotropies. These differences are connected to the conformational changes occurring in the active – inactive interconversion and provide tools for real‐time identification and quantitation of the two protein forms in solution.